2008
DOI: 10.1590/s0100-204x2008000200005
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis of climate change on coffee nematodes and leaf miner in Brazil

Abstract: -The objective of this work was to assess the potential impact of climate change on the spatial distribution of coffee nematodes (races of Meloidogyne incognita) and leaf miner (Leucoptera coffeella), using a Geographic Information System. Assessment of the impacts of climate change on pest infestations and disease epidemics in crops is needed as a basis for revising management practices to minimize crop losses as climatic conditions shift. Future scenarios focused on the decades of the 2020's, 2050's, and 208… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 6 publications
0
51
0
10
Order By: Relevance
“…One of such limitations is that most of the studies consider crops are free of insects, diseases and weeds (Lal et al, 1998;Streck et al, 2006), but some studies have demonstrated that plant pests increase in climate change scenarios (Ghini et al, 2008). These results showed that current modern rice genotypes could be less competitive with red rice in simulated future climates.…”
Section: Resultsmentioning
confidence: 99%
“…One of such limitations is that most of the studies consider crops are free of insects, diseases and weeds (Lal et al, 1998;Streck et al, 2006), but some studies have demonstrated that plant pests increase in climate change scenarios (Ghini et al, 2008). These results showed that current modern rice genotypes could be less competitive with red rice in simulated future climates.…”
Section: Resultsmentioning
confidence: 99%
“…The infestation of L. coffeella will increase on coffee crops under future scenarios when compared with the climatological normal from 1961-1990(Ghini et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Some countries, traditionally coffee producers, are expected to suffer drastic impacts on the quantity and quality of coffee production, due to climate changes and global warming, related to extreme climate events, especially high air temperatures and changes in the amount and pattern of rainfall (Eakin et al, 2006;Schroth et al, 2009;Tucker et al 2010;Davis et al, 2012;Baca et al, 2014;Bunn et al, 2015;Ovalle et al, 2015), as well as the probable higher incidence of plagues and diseases (Ghini et al, 2008;Jaramillo et al 2009;Moraes et al, 2012;Mendes et al, 2012). In fact, modeling studies have foreseen dramatic effects of environmental changes on the world's coffee supply, mostly linked to an increase in air temperature and considering C. arabica.…”
Section: Introductionmentioning
confidence: 99%